サリドマイド胎芽病による上肢障害者の住宅における生活行為に関する研究 - 小川 信子; 阿蘇 道子; 栢森 良二; 小川 卓二; 山本 一裕; 水村 容子 (住宅総合研究財団研究年報, 1999)
The aim of this paper is to study about conditions of housing environments for people with congenital upper limb disabilities, focusing on pains and burdens that have been happened to their bodies when they manage activities of daily lives in pre-built environments for able-body people. The subject of this study is people with Thalidomide-induced upper limb disabilities both in Japan and Sweden. From the results of this study, it is become clear that 8 Japanese subjects hold some pains with their bodies, on the other hand, all subjects of 6 Swedish hold pains with their neck and back, however only 1 subject has some aches. Furthermore, the pains when they deal with daily activities divide into 4 types as follows, ①pains with feet, ② pains with back, ③ pains and numbnesses with hands and fingers and ④pains with neck and back of neck. In Japan, frequencies of occurrence of pains with feet, back, hands and fingers are high. Though those frequencies are low in Sweden, pains with neck and back of neck happen to their bodies frequently. About house adaptations, Swedish subjects use technical aid services and developed housing arrangements to make up with upper limb disabilities, however, a few Japanese subjects reform their houses and they devise the contents of adaptations and pay money by themselves. From above-mentioned results, after this we would like to make concrete conditions of housing arrangements for people with upper limb disabilities, and also consider about technical aid systems that people with disabilities could introduce easily, referring to the examples of foreign countries including Sweden. 本研究は，サリドマイド胎芽病による先天性上肢障害者（以下サリドマイド者とする）を研究対象とし，下肢で立ち上肢で作業することを前提として計画されている既存の住環境の中で生活行為の処理に際し，身体にどのような痛み・負担が生じているか，といった点に着目し上肢障害を配慮した住環境の整備条件を検討するものである。そして，身体の痛み・負担の発生状況および住環境の整備条件の検討に際し，我が国とスウェーデンのサリドマイド者を対象者として調査を実施した。両国における調査の結果，現在の身体状況は日本の対象者8名が複数の身体の痛みを抱えているのに対し，スウェーデンでは6名全員が首・背中・腰などの痛みを訴える一方，複数の痛みを持つ者は1名のみであった。また，生活行為の処理に伴う痛み・負担に関しては，(1)足の痛み，(2)腰の痛み，(3)手や指の痛みやしびれ，(4)首および首の後ろ側の痛み，などの症状が発生している状況が判明した。日本では，足・腰の痛みに併せて，手や指の痛みやしびれを訴える頻度が高かったのに対し，スウェーデンでは足・腰に痛みの発生頻度は低く，また手や指の痛みもほとんど見受けられなかったが，首および首の後ろ側の痛みを訴える場面が頻繁に見受けられた。住環境の整備に関しては，スウェーデンではテクニカルエイドサービスの利用を通じて環境整備が進んでいた一方，日本では住宅改造はあまり行なわれず，改造している者の場合も，改造内容の考案および費用負担は自己で行なっていた。本研究からは，以上の状況が判明したが，今後は，本研究で得た知見を生かし，現在生じている身体の痛み・負担が2次障害となることを防ぎ，快適に生活行為が処理できる住環境の整備条件の具体化に努め，それと同時に，スウェーデンをはじめとした諸外国の事例を参考としながら，当事者にとって利用しやすい住宅改造供給システムの検討を行なっていきたい。